The Viabilities of Freeze-Thaw Pasundan-Bull Sperms After a Short-Term Exposure to Media with Different pHs - Widyastuti, R.; Haq, N. M. D.; Pristihadi, D. N.; Wahyudin,; Maheshwari, H.; Sumantri, C.; Boediono, A. (Tropical Animal Science Journal, 2022)
External pH is crucial in preserving sperm viability and ensuring fertilization during in vitro conditions. The purpose of this study was to determine the maximum pH value that can be tolerated by frozen-thawed Pasundan bull sperms and the effect on sperm quality. Around 250x106 sperms/mL of frozen-thawed Pasundan bull sperms were divided into ten equal aliquots, and each was diluted in the medium within a particular pH value. HCL or NaOH was added to the buffer media to create ten different solutions with varying pH values of 3, 4, 5, 6 as acidic, 7.2-7.4 as a control, and 8, 9, 10, 11, and 12 as alkaline. Furthermore, the samples were incubated for 5 minutes at room temperature within a particular pH medium before being immediately supplemented with a buffered medium to achieve a pH of 7.2-7.4. After 10 minutes of incubation at room temperature, all parameters were assessed. The results showed that sperm motility, viability, normal morphology, and acrosome intactness in sperms incubated in the acidic or alkaline media were significantly lower compared to control (p